The Effect of Social Media Culture and Knowledge Transfer on Performance - Dahlena Sari Marbun; Azuar Juliandi; Sulaiman Effendi (Budapest International Research and Critics University, 2020)
Internet-based social media has become a part of people's lives in this era. Many people use Facebook, Whatsapp, LinkedIn, Blog and other social media to interact with each other. With social media, people exchange information and share experiences in cyberspace. Moreover, nowadays social media has become part of the organizational culture in the workplace. This study aims to analyze: (1) the influence of social media culture on knowledge transfer; (2) the influence of social media culture on work performance; and (3) the effect of knowledge transfer on work performance. The research sample consisted of 300 employees. data collection using a questionnaire. Meanwhile, the data analysis technique used partial least square. The results show that: (1) the influence of social media culture on knowledge transfer is positive and significant; (2) the influence of social media culture on work performance is positive and significant; and (3) the effect of knowledge transfer on work performance is also positive and significant.